1999
DOI: 10.1136/hrt.82.6.731
|View full text |Cite
|
Sign up to set email alerts
|

Decreased amplitude of left ventricular posterior wall motion with notch movement to determine the left posterior septal accessory pathway in Wolff-Parkinson-White syndrome

Abstract: (Heart 1999;82:731-739)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Other methods that have been employed to detect the AP include M-mode echocardiography, phase analysis of 2-dimensional echocardiographic images, Doppler myocardial imaging, and TDI. [10][11][12][13][14][15][16][17] These methods have focused mainly on abnormal ventricular motion. Previous authors have, for example, analyzed the time-sequential changes in ventricular wall motion in WPW syndrome using TDI in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods that have been employed to detect the AP include M-mode echocardiography, phase analysis of 2-dimensional echocardiographic images, Doppler myocardial imaging, and TDI. [10][11][12][13][14][15][16][17] These methods have focused mainly on abnormal ventricular motion. Previous authors have, for example, analyzed the time-sequential changes in ventricular wall motion in WPW syndrome using TDI in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients with Type A WPW, this early anterior motion is accompanied by paradoxical anterior motion of the interventricular septum [28]. It has been reported that the amplitude of LV posterior systolic wall motion is reduced when the pathway is located on the LV side, especially with left posterior septal accessory pathway [29].…”
Section: M-mode Echocardiographymentioning
confidence: 99%
“…Earlier echocardiographic studies demonstrated that left posteroseptal accessory pathways are associated with abnormal left ventricular posterior wall motion [13] and that right anterior or right posteroseptal pathways produce abnormal interventricular septal motion [2, 4–6]. Since these studies predated the era of catheter ablation, localization of accessory pathways was based solely on electrocardiographic criteria [7].…”
Section: Introductionmentioning
confidence: 99%